Me, us, and them Testing sociometer theory in a socially diverse real-life context. [article]. - Reitz, Anne K.
Although numerous studies have emphasized the role evaluations by others play for people's self-esteem, the perspective of others and the social diversity of real-life contexts have largely been ignored. In a large-scale longitudinal study, we examined the link between adolescents' self-esteem and their self- and peer-perceived popularity in socially diverse classrooms. First, we tested the competing directions of effects predicted by sociometer theory (i.e., peer-perceived popularity affects self-esteem, mediated by self-perceived popularity) and the self-broadcasting perspective (i.e., self-esteem affects peer-perceived popularity). Second, we examined differential effects of popularity in the own social group ("us") versus others ("them") by using immigrant status groups (i.e., immigrants versus host-nationals). We examined 1,057 13-year-old students in 3 annual waves. Cross-lagged analyses revealed that popularity among peers of the in-group but not among peers of the out-group prospectively predicted self-esteem, which was mediated by self-perceived popularity. Self-esteem in turn prospectively predicted self- but not peer-perceived popularity. In sum, the findings provide support for sociometer theory and a conscious sociometer mechanism but no support for the self-broadcasting perspective. The findings further demonstrate that the sociometer was more responsive to popularity in immigrant status in- than out-groups. In conclusion, the findings underscore the need to consider the perspective of others and their social group memberships to better understand the complexities of the link between self-esteem and popularity. -- (from the authors)